Impact of preterm birth on kidney health and development - Deffrennes, Sara; Rayyan, Maissa; Fidlers, Tom; van den Heuvel, Lambertus; Levtchenko, Elena; Arcolino, Fanny Oliveira (Frontiers in Medicine, 2024)
Preterm birth, defined as birth before the gestational age of 37 weeks, affects 11% of the newborns worldwide. While extensive research has focused on the immediate complications associated with prematurity, emerging evidence suggests a link between prematurity and the development of kidney disease later in life. It has been demonstrated that the normal course of kidney development is interrupted in infants born prematurely, causing an overall decrease in functional nephrons. Yet, the pathogenesis leading to the alterations in kidney development and the subsequent pathophysiological consequences causing kidney disease on the long-term are incompletely understood. In the present review, we discuss the current knowledge on nephrogenesis and how this process is affected in prematurity. We further discuss the epidemiological evidence and experimental data demonstrating the increased risk of kidney disease in these individuals and highlight important knowledge gaps. Importantly, understanding the intricate interplay between prematurity, abnormal kidney development, and the long-term risk of kidney disease is crucial for implementing effective preventive and therapeutic strategies.